Phenotypic and Genotypic Characterization of Multidrug-resistant Escherichia coli and Klebsiella pneumoniae Isolated from Women with Urinary Tract Infections in Mosul City - Younus, Nada Khairi (Iraqi Journal of Science, 2024)
This study was established to discover and determine multidrug-resistant Escherichia coli and Klebsiella pneumoniae from women suffering urinary tract infections, specifically in Mosul city. A total of 62 E. coli and 32 K. pneumoniae bacterial isolates were considered for this study. All isolates were characterized using standard bacterial culture methods, including culture on MacConkey agar, Eosin Methylene Blue agar and biochemical tests. Also antibiotic sensitivity test using standard disc method for different antibiotics and also special discs to detect ESBL activity were carried out, in addition to PCR as molecular identification tool. The results showed that most isolated E. coli and K. pneumoniae demonstrated MDR resistance pattern with highest resistance recorded for E. coli to tetracycline 62/62 (100%), trimethoprim/sulfamethoxazole 60/62 (96.8%), gentamycin 51/62 (82.3%) and azithromycin 50/62 (80.7%). While K. pneumoniae recorded high resistance to nalidixic acid 32/32 (100%) and tetracycline 26/32 (81.2%). On the other hand, imipenem was the only one that showed ultimate sensitivity for all E. coli and K. pneumoniae isolates. Furthermore, the current results revealed that 68/94 (72.3%) of the studied isolates have ESBL activity. The results for molecular studies confirmed that E. coli and K. pneumoniae have resistance genes with dominated CTX-M gene, followed by SHV and finally TEM gene. The study concluded that E. coli and K. pneumoniae with MDR feature are serious threat to women with UTIs and all necessary measures ought to be performed in order to reduce the antibiotic resistance.